Direct ink writing of cordierite ceramics with low thermal expansion coefficient. Issue 4 (April 2022) - Chen, Zhe; Xu, Zhongkai; Cui, Fengdan; Zhang, Jian; Sun, Xiaohong; Shang, Yunpeng; Guo, Ruisong; Liu, Nan; Cai, Shu; Zheng, Chunming
Highlights: A printable formulation for preparing cordierite ceramics by direct ink writing was developed. The near-net size sintering of cordierite ceramics was achieved by means of the compensation for shrinkage via the volume expansion derived from the phase transition. The average coefficient of thermal expansion of cordierite ceramics sintered at 1400 °C in the temperature range of 30-1000 °C was 1.69×10 −6 °C −1 . Abstract: Since the application of cordierite ceramics is limited by the disadvantages of traditional preparation techniques, 3D printing technology provides the only choice for the rapid preparation of cordierite ceramics with highly complex structures. In this work, the fabrication of cordierite ceramics with complex structures was achieved by direct ink writing. The near-net-shape of cordierite ceramics was realized by the volume expansion caused by the phase transformation. A cordierite ceramic with an average shrinkage rate of 1.58 % was obtained at 1400 °C. The low shrinkage avoids design and manufacturing procedures carried out for dimensional and alignment errors. In addition, the coefficient of thermal expansion was as low as 1.69 × 10 −6  °C −1 . The effect of configuration on the thermal behavior of cordierite ceramics is understood by analyzing the phase composition and microstructure. The cordierites ink reported in this work offers additional possibilities for the production of novel complex structures.